THE ROLE OF THE CONCEPT WITHIN THE FRAMEWORK OF LINGUACULTURAL RESEARCH (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Linguocultural studies, as a section of linguistics in a super-large aspect, its identification and mobile development is a product of our century, specifically, it is conditioned by the main scientific paradigm in the process of modern language development. The concept as a subject of linguocultural studies, the study of concept has a huge impact on the consideration of national culture. This article is devoted to identifying the role of the concept within the framework of linguocultural studies.